Evaluation of hesperidin as a potential larvicide against Culex pipiens with computational prediction of its mode of action via molecular docking - Abdullah Haikal; Mahmoud Kamal; Eslam M. Hosni; Yhiya Amen (Scientific Reports)
Abstract Hesperidin, a natural flavanone glycoside predominantly found in citrus fruits, has gained attention for its wide-ranging biological activities, including potential insecticidal properties. Culex pipiens, commonly known as the northern house mosquito, is a major vector of several human pathogens, such as the West Nile virus and filariasis, making it a key target in the fight against vector-borne diseases. In this study, we evaluated the larvicidal activity of Hesperidin against Culex pipiens larvae, assessing its potential as an alternative to chemical insecticides. Hesperidin demonstrated potent larvicidal effects, with a lethal concentration 50 (LC50) of 570.3 ± 0.04 µg/mL, outperforming the conventional insecticide Chlorpyrifos 588.3 ± 0.28 µg/mL in efficacy. Molecular docking simulations revealed a strong binding affinity between Hesperidin and crucial neuroreceptors in Culex pipiens, particularly acetylcholinesterase (AChE), a key enzyme involved in nerve signal transmission. The interaction between Hesperidin’s hydroxyl groups and the AChE enzyme’s active site suggests that AChE inhibition is the primary mechanism driving Hesperidin’s insecticidal action. These findings position Hesperidin as a promising, environmentally friendly alternative to synthetic insecticides. However, further research is needed to assess its toxicity to non-target organisms and optimize its formulation for broader application in mosquito control.